Control Synthesis of Two-Mass Electromechanical Object - O. F. Opeiko (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper studies a cascade control synthesis for a two-mass electromechanical object. A cascade synthesis allows to determine a quick action of an electric drive speed regulation loop which is necessary for control of the specified mechanical part. A small parameter method is used in the paper. Calculative expressions for relations of loop frequency characteristics have been obtained in the paper. The paper presents a calculative example with the results of the system mathematical simulation.A synthesized system is characterized by robustness because variations in object parameters are acceptable if conditions of the system accessory to the given sets are observed.The proposed method can be applied if an own frequency of elastic vibrations is not very large in comparison with the characteristic frequency of the synthesized system.